REFLECTIONS ON EDUCATING AND TRAINING PROFESSIONALS IN THE CURRENT TIMES: DO WE NEED EDUCATORS OR STREAMERS? - Corrêa, Harrison; Gaya de Figueiredo, Marco Antonio; Gallon Corrêa, Daniela (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
The past 20 years have been life changing. Since mankind witnessed industrial revolutions, there has never been a technological evolution (now coupled to the digital one) in such a short time span. The cost reduction for the production of electronic devices and the emergence of a labor market in the area of information technology were indispensable factors for the immersion of a significant part of the world society into the digital age. Technology companies began to occupy hitherto almost unexplored spaces. With data informatization, many processes became more agile and easier to be monitored and managed. Financial systems have now eliminated part of their physical workstations, replacing them with artificial intelligence. The media and companies of various segments, more adherent to algorithms capable of directing personalized content to each user, experience a new sales cycle. The dissemination of communication networks based on 5G technologies allows for a greater access to internet contents, which are not scarce. People are getting more and more exposed and also more and more willing to be exposed. In the educational sphere, there is an increase in the consumption of information which is not necessarily quality related. Open channels on non-institutional platforms sell ‘miraculous’ methodologies for learning various subjects, ranging from Engineering to Law. But is this really the path to modernize education? The present article aims to reflect on the current scenario, focusing on the Brazilian context, an emerging country with a high population index.